English andFrench pre-service teachers’ perspectives on netflix as a vocabulary improvement tool - ERSİN, PINAR; BAŞKAN, NACİ SERHAT (My University, 2023)
With the widespread use of the Internet and its speed, a number of changes have occurred in media tools. The changes have led to the emergence of video streaming services. The use of these services has changed the way of following media tools. The viewer profile that watches the productions in a certain time interval offered by traditional media has transformed into a viewer profile that watches at the time interval of its choice. Foreign language teaching has also been directly affected by this paradigm shift, which is discussed in the context of media sociology. With the development of video streaming services, it is possible to access many videos instantly in the classroom. as these services operate in different countries, dubbing,localization and subtitles translated in different languages are also available. These services, which offer rich alternative opportunities for language teaching through media, are frequently used in language classrooms. Netflix is the most of popular one. The videos, suitable for use depending on student autonomy and the 21st century skills, fill an important gap in order to vocabulary development. Thus, the present study aims to measure the opinions of pre-service teachers about the contribution of watching TV series and movies on Netflix to their English or French language learning. This descriptive study was conducted at a state university in Istanbul, Turkey. 80 pre-service teachers studying in the 4th grade of English and French LanguageTeaching Departments participated in the study. A 5-point Likert scale developed by Damanik and Katemba (2021) was used as the data collection instrument. It was sent to the pre-service teachers via Google Forms. Data were analyzed by using Jamovi. results will be shared in the presentation in the light of the statistical data. Moreover, limitations of the study and suggestions for further research will be presented.Keywords: Video Streaming Services, Foreign Language Teaching, Vocabulary Improvement, Educational Technologies, Teacher Educaton, E-Learningİmprovement, Educational Technologies, Teacher Educaton, E-Learning
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Yabancı Diller Eğitimi; İngilizce Eğitimi; Fransızca Eğitimi; Social Sciences and Humanities; Education; Education in Foreign Languages; Education in English; Education in French; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Video Streaming Services; Foreign Language Teaching; Vocabulary İmprovement; Educational Technologies; Teacher Educaton; E-Learning